Sistema específico de valoración del riesgo Institucional en la Unidad de Recursos Humanos y Financiero-Contable del Servicio Nacional de Aguas Subterráneas, Riego y Avenamiento - Sánchez-Muñoz, Carolina (Instituto Tecnológico de Costa Rica, 2014)
Risk management is an essential part of a company’s strategy, because it provides a future vision that helps to identify and manage the risks associated with the different activities, tasks and processes of the organization. The objective of this project is to valuate the risks of the different activities, tasks and processes of the Human Resources Unit and the Financial Unit of Senara, and the financial processes of Distrito de Riego Arenal Tempisque, using the SEVRI model, which is the methodology proposed by the Contraloría General de la República.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2014.
Keywords: Normas; Administración; Planeación; Organización; Eficiencia; Eficacia; Gestión de riesgos; Riesgos; Contabilidad; Valoración; Fuentes de información; Estrategia; Cuentas por cobrar